1972
DOI: 10.1177/001440297203800705
|View full text |Cite
|
Sign up to set email alerts
|

Labels and Stigma in Special Education

Abstract: Two notions about the delivery of services to disadvantaged, deprived, and mildly retarded children are advanced: (a) that insufficient attention has been given to the fact that certain~;pecial education labels imply deficiencies UTld shortcomings in children and (b) that no systematic inquiry has been made of children's perceptions of the labels and services offered them. Analyses of data from several studies involving more than 10,000 public school students, graduates, and dropouts; college students; prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…Budoff and Siperstein report that their findings from this study of ninety-six white, sixth grade students indicate that regular students have different levels of acceptance for MR students. The study ha~ regular class peers describe their attitudes towards 11 La beling effects are also discussed by : Dunn, 1968;Gottlieb, 1974;Guskin, 1974;Haywood, 1971;Jones, 1972;MacMillan et. aI, 1974;Mercer, 1971;Miller, 1956;Potter, 1971;Rist, 1970. low achievers.…”
Section: Labeling and The Mentally Retardedmentioning
confidence: 94%
See 2 more Smart Citations
“…Budoff and Siperstein report that their findings from this study of ninety-six white, sixth grade students indicate that regular students have different levels of acceptance for MR students. The study ha~ regular class peers describe their attitudes towards 11 La beling effects are also discussed by : Dunn, 1968;Gottlieb, 1974;Guskin, 1974;Haywood, 1971;Jones, 1972;MacMillan et. aI, 1974;Mercer, 1971;Miller, 1956;Potter, 1971;Rist, 1970. low achievers.…”
Section: Labeling and The Mentally Retardedmentioning
confidence: 94%
“…Studies have used matching and statistical manipulations to control for some of these potentially confounding variables in self-concept research, but none have gone so far as to address all of the variables which this research will consider. (Boersma, Chapman & Battle, 1979;Legette, 1979;McIntyre & Drummond, 1977;Ottenbacher, 1981).19 18These researchers also examined significant others' perceptions: Good & Dembo, 1973;Gottlieb, 1974: Jones, 1972Mayer, 1965;Prieto & McCoy, 1979;Ysseldyke & Foster, 1978. 19Additional studies in self-concept addressing a number of variables have been carried out by: Rosenberg, 1979;Trowbridge, 1972. 124 CHAPTER III…”
Section: Content And/or Methodological Limitations Of Previous Studiementioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations of this study, as reported by Hobbs (1974, included: 1) the involvement of parents in the evaluation and placement process; 2) the search for a less stigmatizing classification system of identifying handicapped pupils for service; and 3) the development of funding formulae which do not require local personnel to label children before services are received. Although Trudeau (1972) and Gallagher et al (1975) cited labeling as a necessary or desirable aspect of classification to assure an appropriate "headcount" for federal funding purposes, the weight of many recent studies including Jones (1972), Krasner (1977), and Reschly (1980) indicates a deleterious effect from the traditional classification system. Notwithstanding, school systems are required to label pupils before funds can be received to provide appropriate services.…”
Section: Larry a Magliocca Robert T Rinaldimentioning
confidence: 99%
“…The medical implications of the diagnosis tend to follow the child throughout school and even after it. These negative labels not only categorize, they impersonalize and dehumanize (Jones, 1972). The result was an "easy out" for special education because the model placed the onus for failure in the child rather than upon the system (Hirshoren et al, 1970).…”
Section: Defining the Problemmentioning
confidence: 99%